The Effect of Bariatric Surgery Volume on General Surgery Outcomes for Morbidly Obese Patients - Katheryn Hope Wilkinson; Ruizhe Wu; Aniko Szabo; Rana Higgins; Jon Gould; Tammy Kindel (Journal of Obesity)
Introduction. Bariatric surgery performed at high volume centers decreases length of stay, cost, and morbidity and mortality. The effect of a high volume of bariatric surgery procedures on outcomes may extend not just to bariatric surgery but to any general surgical procedure in morbidly obese patients. We hypothesized that patients with morbid obesity (body mass index >40 kg/m2) undergoing common, nonbariatric general surgery would have decreased morbidity and mortality at centers performing high volumes of bariatric surgery. Methods. The 2016 National Inpatient Sample (NIS) was used to identify the number of laparoscopic gastric bypass and sleeve gastrectomy performed at each hospital. Hospitals were classified as high volume bariatric hospitals (HVBH) ≥10 reported cases (50 actual)/year or low volume bariatric hospitals (LVBH) <10 reported cases (50 actual)/year, as NIS reports a 20% sample of actual cases. Patients with morbid obesity undergoing laparoscopic or open appendectomy, cholecystectomy, or ventral hernia repair were included for analysis. Propensity scores were developed based on available demographics, comorbidities, and hospital procedure volume. Postoperative complications during the index hospital admission, determined by ICD-10 code, were compared using inverse propensity weights. Differences were considered significant with a p value of <0.05. Results. The total number of general surgery patient cases analyzed was 14,028 from 2,482 hospitals, representing 70,140 admissions. The cohort of patients undergoing operations treated at HVBH were younger (p=0.03) with higher rates of COPD (p=0.04). Patients at LVBH had higher rates of nicotine dependence (p=0.0001) and obstructive sleep apnea (p<0.001). On propensity-weighted analysis adjusting for preoperative comorbidities and hospital procedure volume, there were significantly higher rates of multiple postprocedure complications at LVBH, specifically, postprocedure respiratory failure for patients undergoing elective laparoscopic cholecystectomy, elective ventral hernia repair with mesh and appendectomy. Conclusion. Patients with morbid obesity may have an advantage in having general surgery procedures at HVBH. HVBH may have a volume-outcomes relationship where the hospital and staff familiarity with the management principles required to minimize the postoperative risk associated with morbid obesity and improve patient outcomes.